ANALISIS KOMPARATIF DAN SINTESA TEORI BELAJAR KONVENSIONAL DENGAN TEORI BELAJAR DALAM ISLAM - Muhammad Husni (Nurul Jadid University, 2018)
Learning is a necessity and plays an important role in human life. This is because humans are born as a weak creature who can not do anything and know nothing, he is only equipped with physical and spiritual potential. So it is reasonable to see why and how humans are affected by how they learn. Therefore learning is the